Does pre-incubation in selective-enrichment media improve the detection of diarrheagenic Escherichia coli using the RIDA®GENE PCR? - Neele J. Froböse; Ioana D. Olaru; Julia Sophie Schneider; Wenlan Zhang; Alexander Mellmann; Franziska Schuler; Tobias Grebe; Frieder Schaumburg (Elsevier, 2023)
We aimed to investigate whether a selective pre-PCR enrichment step improves test performance of RIDA®GENE EHEC/EPEC to detect diarrheagenic Escherichia coli from stool samples. Each of the 250 stool samples was analyzed for the presence of stx1/2 and eae both with and without pre-PCR enrichment in selective broth. In comparison to a reference method, sensitivities for stx1/2 and eae with and without pre-PCR enrichment were 84% (95%CI 70-93) and 89% (stx1/2, 95%CI 76-96), and 71% (95%CI 58-81) and 72% (eae, 95%CI 60-82), respectively. Specificity exceeded 97% for both methods and target genes. In summary, pre-PCR broth enrichment did not improve test performance.